Лінгвістична ситуація двомовності і контактно обумовлене явище інтерференції - Козаченко, А.Н. (Культура народов Причерноморья, 2003)
В статье рассматриваются лингвистические основы исследования явления интерференции, охарактеризовано современное состояние развития контактологии, даны определения различных ситуаций билингвизма. Сделано вывод о том, что ситуация искусственного билингвизма является наиболее благоприятной для интенсивного проявления интерференции. Linguistic research basis of interference are under cosideration in this article. The present day condition of the development of contaktology is characterized, and the definitions of various billingual situation are given as well. The conclusion that ar-tificial bilingual situation is the most favourable for an intensive development of interference was made.